A Meta-Analysis of Randomized Clinical Trials of Runzao Zhiyang Capsule in Chronic Urticaria. (17th September 2022) - Ye, Shengzhen; Zhang, Xueer; Ling, Guihua; Xiao, Xianjun; Huang, Dan; Chen, Mingling
Abstract : Chinese herbal medicine has many advantages in the treatment of chronic urticaria (CU). Herein, we evaluated the efficacy and safety of the Runzao Zhiyang (RZZY, Chinese patent herbal medicine capsule) capsule for CU through a meta-analysis of randomized clinical trials (RCTs). This meta-analysis included 17 RCTs involving 1, 760 patients. RZZY capsule combined with conventional drugs showed a better clinical total effective rate (risk ratio (RR) = 1.20, 95% confidence interval (CI) (1.15, 1.24), P < 0.00001 ), significantly reduced the adverse reaction rate [RR = 0.68, 95% CI (0.50, 0.92), P = 0.01 ] and recurrence rate [RR = 0.29, 95% CI (0.18, 0.46), P < 0.00001 ], and improved the life quality of patients (mean difference (MD) = −2.95, 95% CI (−4.32, −1.57), P = 0.0001 ). Meanwhile, the serum Interleukin-4 (IL-4) (MD = −13.83, 95% CI (−23.45, −4.20), P = 0.005 ) and immunoglobulin E (IgE) (MD = −22.99, 95% CI (−31.48, −14.50), P < 0.00001 ) of patients in the intervention group decreased more significantly. In all, the RZZY capsule has potential therapeutic advantages and is relatively safe for CU. However, we are cautious about the conclusion, which needs to be further confirmed by more large samples, multicenter, and high-quality research in the later stage.